Dabrafenib and trametinib induced pancreatitis: a case report and review of the literature. Issue 2 (7th October 2020) - Ogliari, Francesca R.; Rodolfo Masera, Giovanni L.; Gueli, Rossana; Chini, Claudio
Abstract : Approximately 50% of melanomas are characterized by BRAF mutation (V600E in 90% of cases), that predicts more aggressive behaviour. This mutation is the target of dabrafenib, an anti-BRAF tyrosine-kinase inhibitor (TKI), that together with trametinib, anti-MEK TKI, is approved for first-line treatment of metastatic melanoma due to significant benefit in overall and progression-free survival. Most common treatment-related adverse events are pyrexia, chills, fatigue, rash, nausea, vomiting, and diarrhoea. This case report aims to present another less common adverse event of combined anti-BRAF and anti-MEK treatment. Our patient, after 4 months on target-therapy, experienced sudden deep abdominal pain. At the initial work-out at the emergency department, increase in serum lipase was detected and radiological findings were consistent with acute pancreatitis. Admitted to the hospital, other causes were ruled out and target-therapy was discontinued with symptoms improvement. Radiological and clinical follow-up was performed and a diagnosis of drug-induced pancreatitis was made. After few days of medical support with analgesia and antibiotic, the patient felt better and was discharged; target-therapy was permanently interrupted. Searching the literature, not so many cases of iatrogenic pancreatitis are described with this TKI combination, therefore, we have reported it as a rare but life-threatening adverse event that should be investigated whenever conceivable.